Nová metoda lécby muzské neplodnosti: perkutánní transfemorální embolizace varikokély Vilanem 500 - Janík, V; Kolihová, E; Zvĕrina, J; Kawaciuk, I (Rozhledy v chirurgii, 1989)
The authors describe a new method of treatment of male infertility. In 25 men aged 19-45 years with varicocele, after percutaneous transfemoral catheterization, embolization of the spermatic vein with the Czechoslovak preparation Vilan 500 (hydrolyzed co-polymer of polyvinyl acetate and polyvinyl alcohol in 96% ethyl alcohol) was performed. Six patients were treated on account of marked subjective complaints and 19 because of reduced fertility. Of these in 16 after embolization the spermiogram improved. The authors describe the diagnostic procedure, the technique of embolization, its complications and results. The described method is simple, safe, effective and as compared with other embolization methods it is cheaper.
Keywords: Embolization, Therapeutic; Middle Aged; mužská infertilita; mužské pohlaví; dospělí; Humans; polyvinyly; varikokéla; Adult; Infertility, Male; Varicocele; terapeutická embolizace; lidé; Male; Polyvinyls; lidé středního věku